Analysis of 18 bp Ins/Del at -2549 polymorphism of the vascular endothelial growth factor gene in patients with systemic lupus erythematosus - Évelin M. Cassemiro; Daiani Cristina C. Alves; Daniel O. Freire; Lusitano B. Ferreira; Carlos Eduardo C. Lins; Izabel Cristina R. Silva; Rodrigo Haddad (Sociedade Brasileira de Patologia Clínica, 2017)
ABSTRACT Systemic lupus erythematosus (SLE) is considered an autoimmune disease characterized by the action of autoantibodies, which cause chronic inflammation in various tissues of the body. Considering the vascular endothelial growth factor (VEGF) participation in the development of inflammation, this study aimed to evaluate the frequency of the polymorphism at the -2549 position (Ins/Del 18pb, rs35569394) in patients with SLE and in healthy individuals. No statistical differences were found when comparing the allele and genotype frequencies between patients and controls, suggesting that there is no association between the studied polymorphism and the development of SLE.